Robbery of the Wachovia branch at Wake Forest College campus, 1958. - (:unkn) unknown (Forsyth County Public Library, 2009)
WSJ 4-4-58 p.1.
Robbery of the Wachovia branch at Wake Forest College campus, 1958. Fred Holmes gives his account of the robbery.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth